Analisis Pengaruh Kualitas Pelayanan Badan Pertanahan Nasional (BPN) terhadap Kepuasan Masyarakat di Daerah Istimewa Yogyakarta - Eny Sulistyowati (Jurnal Maksipreneur, 2014)
In the business world the life of customer satisfaction is an absolute must be the goal to achieve success. Due to the satisfaction of the consumer or customer achieved will bring many benefits to producers or lembaga.Salah one thing that consumers in the purchase consideration is the quality of services provided by the National Land Agency (BPN) DIY. The level of public satisfaction/service users occur after comparing reality and perceived performance or results with expectations and perceptions about these services. If the same customer perceived reality in the hope that customers want the satisfaction occurs, if the fact that the perceived lower than desired expectations of customers, the dissatisfaction will occur and if accepted the fact that a higher than desired expectations of customers then they will feel very satisfied. To measure customer satisfaction can one use that service quality can be measured with variable responsiveness, assurance, tangible, empathy, and reliability. From the results it was found that five variables research customer service has almost the same value yanh (average less than 1) the expected service with perceived service. This suggests that public service users BPN had enough satisfaction.